Why I Am Worried about My Post MPH-degree Life - A Commentary - Marissa Berrier (University of North Florida, 2013)
Public health is an area where we will always need professionally-prepared people, but despite the aging of the public health workforce, some soon-to-graduate MPH students are concerned that there might not be a place for them. Perhaps now more than ever public health professional programs and schools need to devote increased resources toward internships, skill development, and job placement.